Evaluation of Some Insecticides Against Brown Plant Hopper, Nilaparvata lugens (Stal) in Rice, Oryza sativa L. - Seni, Atanu; Naik, Bhima Sen (International Journal of Bio-resource and Stress Management, 2017)
A field experiment was conducted to determine the comparative efficacy of some newer insecticides with some conventional insecticides against brown plant hoppers (BPH) in rice during kharif 2014 and rabi, 2014–2015. The treatments include: Thiamethoxam 25 WG @ 37.50 g a.i. ha-1, Lamda cyhalothrin 5 EC @ 30 g a.i. ha-1, Pymetrozine 50 WG @ 150 g a.i. ha-1, Buprofezin 25 SC @ 250 g a.i. ha-1, Glamore (Imidachloprid 40+Ethiprole 40% w/w) 80 WG @ 100 g a.i. ha-1, Dinotefuran 20 SG @ 40 g a.i. ha-1, Acephate 75 SP @ 564 g a.i. ha-1, untreated control and a basal application of fipronil 0.3 G @ 25 kg ha-1 was made once at 25 DAT in all treatments except untreated control. All the treatments were effective for hoppers management than control. The overall data revealed that the Pymetrozine 50 WG @ 150 g a.i. ha-1 recorded significantly higher percent reduction of hoppers and higher grain yield than the other treatments. Pymetrozine 50 WG @ 150 g a.i. ha-1 treated plot also had more number of spiders (3.71 spiders 10 hills-1 after 10 DAT of last spray) than other chemical treated plots. In cost benefit ratio it is observed that the Pymetrozine 50 WG @ 150 g a.i. ha-1 (1:4.18) and Lamda cyhalothrin 5 EC @ 30 g a.i., ha-1 (1:4.46) treated plots had more return than expenditure.